Preliminary in vitro cytotoxic evaluation of Uncaria gambier (Hunt) Roxb extract as a potential herbal-based pulpotomy medicament - Bee Chin Tan; Alida Mahyuddin; S. Nagarajan M. P. Sockalingam; Ahmad Shuhud Irfani Zakaria (BMC, 2023)
Abstract Background The downfall of formocresol as a pulpotomy medicament highlights the importance of cytotoxic evaluation and the establishment of a safe concentration of dental material prior to its usage in the oral cavity. Uncaria gambir is an herbal plant that possesses antimicrobial, anti-inflammatory and antioxidant properties, suggesting its potential as an alternative medicament for pulpotomy. However, there are not many studies published on its cytotoxicity, with some using non-standardised techniques and reported variable outcomes. Here, we investigated the concentration and time-dependent toxicity of Uncaria gambir extract towards the M3CT3-E1 cell line and compared it with the gold standard pulpotomy medicament: mineral trioxide aggregate (MTA). Methods Uncaria gambir extracts at concentrations ranging from 1000 to 7.8 µg/ml and MTA eluates at 4- and 48 h setting times were prepared. 10% dimethyl sulfoxide (DMSO) and culture media were used as positive and negative controls respectively. Cell viability on days 1, 2, 3 and 7 was analysed using Alamar Blue and Live and Dead Cell assay. Any morphological cellular changes were evaluated using transmission electron microscopes (TEM). Data were analysed using a two-way mixed Analysis of Variance (ANOVA). Results The interaction between the concentration and exposure time on the fluorescence intensity of Uncaria gambir extract and MTA 48 h was found to be statistically significant (p < 0.001). No cytotoxic effects on the cells were exerted by both MTA 48 h and Uncaria gambir extract at a concentration below 500 µg/mL. TEM analysis and Live and Dead Cell assay for both materials were comparable to the negative control. No significant differences in fluorescent intensity were observed between Uncaria gambir extract at 500 µg/mL and MTA 48 h (p > 0.05). Conclusion Uncaria gambir extracts at a maximum concentration of 500 μg/mL are non-cytotoxic over time and are comparable to the MTA.